Flight Burst Duration as an Indicator of Flight Ability and Physical Fitness in Two Species of Tephritid Fruit Flies. Issue 5 (28th September 2020) - Manoukis, Nicholas C; Carvalho, Lori A F N
Abstract: We introduce a method to quantify flight ability and physical fitness of individual fruit flies which we term 'Flight Burst Duration' (FBD). This consisted of tethering individual insects by the dorsal thorax using a vacuum and measuring the length of time the insect beats its wings while suspended off a surface. Consecutive measurements with Bactrocera dorsalis Hendel (Dipera: Tephritidae) and Zeugodacus cucurbitae Coquillett (Diptera: Tephritidae) in the same day and across days indicated that a single measurement was sufficient, and that FBD was consistent and repeatable. Insects under stress from starvation displayed shorter FBD over time, and we suggest that the measure also relates to the physical condition or survival fitness of the individual. Though somewhat laborious and time-consuming, we propose that FBD can be useful for research studies requiring individual-level phenome data and for obtaining estimates quality and dispersive movement for insects.